Abordagens meta-heurísticas para clusterização de dados e segmentação de imagens - Queiroga, Eduardo Vieira (2017)
Many computational problems are considered to be hard due to their combinatorial nature. In such cases, the use of exaustive search techniques for solving medium and large size instances becomes unfeasible. Some data clustering and image segmentation problems belong to NP-Hard class, and require an adequate treatment by means of heuristic techniques such as metaheuristics. Data clustering is a set of problems in the fields of pattern recognition and unsupervised machine learning which aims at finding groups (or clusters) of similar objects in a benchmark dataset, using a predetermined measure of similarity. The partitional clustering problem aims at completely separating the data in disjont and non-empty clusters. For center-based clustering methods, the minimal intracluster distance criterion is one of the most employed. This work proposes an approach based on the metaheuristic Continuous Greedy Randomized Adaptive Search Procedure (CGRASP). High quality results were obtained through comparative experiments between the proposed method and other metaheuristics from the literature. In the computational vision field, image segmentation is the process of partitioning an image in regions of interest (set of pixels) without allowing overlap. Histogram thresholding is one of the simplest types of segmentation for images in grayscale. Thes Otsu’s method is one of the most populars and it proposes the search for the thresholds that maximize the variance between the segments. For images with deep levels of gray, exhaustive search techniques demand a high computational cost, since the number of possible solutions grows exponentially with an increase in the number of thresholds. Therefore, metaheuristics have been playing an important role in finding good quality thresholds. In this work, an approach based on Quantum-behaved Particle Swarm Optimization (QPSO) were investigated for multilevel thresholding of available images in the literature. A local search based on Variable Neighborhood Descent (VND) was proposed to improve the convergence of the search for the thresholds. An specific application of thresholding for electronic microscopy images for microstructural analysis of cementitious materials was investigated, as well as graph algorithms to crack detection and feature extraction.